Alginate oligosaccharides can maintain activities of lysosomes under low pH condition - Ra-Mi Park; Ngoc-Han Thi Nguyen; Su-Min Lee; Yang-Hoon Kim; Jiho Min (Scientific Reports, 2021)
Abstract The objective of this study was to report that lysosome extracted from egg white could be used as a drug through oral administration for treating diseases by using pH sensitive alginate oligosaccharides. Lysosome-alginate oligosaccharides composite were formulated for oral administration of lysosomes. The dissolution test confirmed the availability of the oral dosage form. When lysosome were used as an independent drug, the activity of protein was lost due to influence of low pH. Its antibacterial activity was also remarkably reduced. However, when lysosome-alginate oligosaccharides composite form was used, antimicrobial activity of lysozyme was maintained. At low pH, a gel-like matrix was formed by alginate oligosaccharides to protect the lysosome. When the pH was increased, alginate oligosaccharides were dissolved and the lysosome was released. SDS–polyacrylamide gel electrophoresis analysis of released lysosomes revealed that alginate oligosaccharide could effectively protect the lysosome from degradation or hydrolysis under acidic conditions for at least 2 h. The results of this study are important for application of lysosomes as therapeutic agents, and also it was confirmed that alginate oligosaccharides have potential as direct delivery system for the oral application of protein derived therapies.